2015
DOI: 10.1021/acs.organomet.5b00450
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenes Bridged by Ethylenediamino Thiophene: Varying Charge Transfer Properties in a Series of 3,4-Di-N-substituted 2,5-Diferrocenyl Thiophenes

Abstract: A series of 3,4-di-N-substituted 2,5-diferrocenyl thiophenes is reported with the aim to explore the electronic interaction between the organometallic termini over their bridging unit. The syntheses of thiophenes 1−4 were implemented on the basis of 2,5-diferrocenyl-3,4-dinitrothiophene (1), which is accessible within a Pd-promoted Suzuki− Miyaura C,C cross-coupling reaction. Reduction of the nitro functionalities and a subsequent methylation or condensation reaction gives 2,5-diferrocenyl-3,4-bis(N, (4) could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…[f] Reduction of the nitro groupo ccursa tE8 n ' = À1555 mV (DE p = 65 mV; i pa /i pc = 0.99). of the N,N-dimethylaminophenyl group [37,39] (10 a, E8 3 ' = 955 mV) or the reduction of the nitro group [71] (10 f, E8 n ' = À1555 mV;T able 1), whereas the irreversible reduction process at E pc = À1350 mV in 10 f may be caused by some decomposition of follow-up products formed during the electrochemical measurement. However,w hen the potentialr ange wasr estricted to À1000 to 500 mV,amore reversible behavior for both oxidations of 10 f was observed ( Figure 4).…”
Section: Electrochemistrymentioning
confidence: 99%
“…[f] Reduction of the nitro groupo ccursa tE8 n ' = À1555 mV (DE p = 65 mV; i pa /i pc = 0.99). of the N,N-dimethylaminophenyl group [37,39] (10 a, E8 3 ' = 955 mV) or the reduction of the nitro group [71] (10 f, E8 n ' = À1555 mV;T able 1), whereas the irreversible reduction process at E pc = À1350 mV in 10 f may be caused by some decomposition of follow-up products formed during the electrochemical measurement. However,w hen the potentialr ange wasr estricted to À1000 to 500 mV,amore reversible behavior for both oxidations of 10 f was observed ( Figure 4).…”
Section: Electrochemistrymentioning
confidence: 99%
“…Ferrocenyl-substituted pyrroles have been investigated in electron-transfer studies (for example, see: Hildebrandt et al, 2011a,b;Hildebrandt & Lang, 2011Pfaff et al, 2013Pfaff et al, , 2015aKorb et al, 2014;Yu-Qiang et al, 2015), demonstrating that pyrroles are well suited to examine intramolecular metalmetal interactions in mixed-valent species, when compared to other heterocycles such as furan, thiophene, phosphole or siloles (Hildebrandt et al, 2013(Hildebrandt et al, , 2011Pfaff et al, 2015a,b;Lehrich et al, 2014;Miesel et al, 2013Miesel et al, , 2015Speck et al, 2012aSpeck et al, , 2014Speck et al, , 2015. As has been shown in the study of 3,4diferrocenyl pyrroles [3,4-Fc 2 -c C 4 H 2 NR; Fc = Fe( 5 -C 5 H 4 )( 5 -C 5 H 5 ); R = Ph, SO 2 -4-MeC 6 H 4 , Si i Pr 3 ; Korb et al, 2014;Goetsch et al, 2014], the compounds showed a low degree of delocalization between the formal C,C double and C,C single bonds, in contrast to 2,5-substituted pyrroles (Korb et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The electrochemical properties of 3a , 5a , b , 5c , 6a – c , and 7 were studied by using cyclic voltammetry (CV) and square‐wave voltammetry (SWV) and by in situ UV/Vis/NIR spectroelectrochemistry ( 3a and 6a – c ) (Figures , , , , and S68–S70; Tables and ). The electrochemical measurements were performed under argon in dichloromethane solutions containing [ n Bu 4 N][B(C 6 F 5 ) 4 ] (0.1 mol L –1 ) as supporting electrolyte , , . The weak coordinating counterion [B(C 6 F 5 ) 4 ] – is known to stabilize highly charged species in solution.…”
Section: Resultsmentioning
confidence: 99%